Adipostatins E-J, new potent antimicrobials identified as inhibitors of coenzyme-A biosynthesis - Gómez Rodríguez, Lyanne (2020)
Phosphopantetheine is a key structural element in biological acyl transfer reactions found embedded within coenzyme A (CoA). Phosphopantothenoylcysteine synthetase (PPCS) is responsible for installing a cysteamine group within phosphopantetheine. Therefore, it holds considerable potential as a drug target for developing new antimicrobials. In this study, we adapted a biochemical assay specific for bacterial PPCS to screen for inhibitors of CoA biosynthesis against a library of marine microbial derived natural product extracts (NPEs). Analysis of the NPE derived from Streptomyces blancoensis led to the isolation of novel antibiotics (10-12, and 14) from the adipostatin class of molecules. The most potent molecule (10) displayed in vitro activity with IC50 = 0.93 µM, against S. pneumoniae PPCS. The whole cell antimicrobial assay against isolated molecules demonstrated their ability to penetrate bacterial cells and inhibit clinically relevant pathogenic strains. This establishes the validity of PPCS as a pertinent drug target, and the value of NPEs to provide new antibiotics.